The Effect of Person-Job Fit and Work-Life Balance on Job Satisfaction and Employee Performance at Puskesmas Kubu I Karangasem Bali - Putu Ayu Ananda Puspasari Kartika Putri; Ni Luh Putu Agustini Karta; Ni Ketut Dewi Irwanti; Amir Karimi (Management Department Universitas Islam Negeri Sumatera Utara, 2025)
The increasing complexity of workplace demands and individual expectations has made the alignment between Person-job fit and work-life balance have emerged as key concerns in contemporary organizational management. This study examines how the alignment between individual characteristics and job requirements, together with employees' ability to balance work and personal life, affects job satisfaction and ultimately influences employee performance at Puskesmas Kubu. I, Karangasem, Bali. A quantitative approach was employed using path analysis to examine causal relationships, with data collected through a census of 65 employees. The instrument passed validity and reliability tests and was analysed using SPSS v26. Findings reveal: (1) The findings indicate that both person-job fit and work-life balance have a positive and significant impact on job satisfaction and employee performance. In addition, job satisfaction plays a mediating role in strengthening the relationship between person-job fit and employee performance, while it does not function as a mediator in the relationship between work-life balance and performance. Based on these insights, two key recommendations are proposed: first, enhance Person-Job Fit by aligning job roles with individual competencies and needs; second, improve Work-Life Balance policies to sustain employee well-being and performance. Keywords: Job Satisfaction, Performance, Person-Job Fit, Work-Life Balance